The Inhibitory Effects of the Hot-Water Extract of Fermented Shell Ginger (Alpinia speciosa K. Schum.) on Melanogenesis in B16 Mouse Melanoma Cells - YONAHA, Megumi; AOKI, Yumi; FUJIWARA, Yoko; IWABUCHI, Mari; NAGAHATA, Tomomi (Journal of Home Economics of Japan, 2013)
The leaves of the shell ginger (Alpinia speciosa K. Schum.), a common plant in Okinawa, Japan, are often fermented prior to healthy food use. In this study, we investigated the effects of the hotwater extract of fermented shell ginger (HFS) on melanogenesis in B16 mouse melanoma cells. HFS dose-dependently inhibited melanogenesis without affecting cell growth. While HFS did not have an inhibitory effect on tyrosinase activity in a cell-free system, intracellular tyrosinase activity was decreased by HFS-treatment. HFS also reduced tyrosinase expression at the mRNA and protein levels. In addition, HFS decreased mRNA levels of microphthalmia-associated transcription factor (MITF), the major transcription factor in tyrosinase expression. These results indicate that HFS inhibits melanogenesis and that its inhibitory effect on melanogenesis involves a reduction of tyrosinase expression at the transcript level.